Numerical Simulation Study of the Upper Aquifer Impact on the Coalbed Methane Production - Ping, Yue; Simin, Qu; Yafei, Zhang; Jiawei, Tu; Wei, Ning; Jing, Duan (Frontiers in Energy Research, 2022)
The coal-bed methane (CBM) resources in the Qinshui Basin are abundant with exceptional production potential. Coalbed methane wells usually need to be hydraulically fractured to build economical production. However, the exploration and production experiences have showed that the penetration distances of hydraulic fractures in the vertical direction of coal seams are uncertain, which may lead to fracture communication of the layers above and beneath aquifer layers, resulting in divergent production dynamics among coal-bed methane producers. It has been observed that some of the CBM wells in Block M produced significantly more water than other wells in the surrounding area. It is suspected that the hydraulic fracturing among those producers may have communicated the sandstone aquifers. To address the above challenge, this paper investigated the geological characteristics of the aforementioned aquifer and coalbed layers, established a three-dimensional geological model, applied numerical simulation to quantify the influence of the aquifer on the production of the CBM wells, and developed a method to improve the history matching of CBM production simulation with the influence of the aquifer considered. This method has significantly improved the accuracy of the history matching performance and the reliability of the remaining gas study. The results from this study laid the foundation for the subsequent development strategy optimization.